Comparative in vivo evaluation of restoring severely mutilated primary anterior teeth with biological post and crown preparation and reinforced composite restoration - Grewal N; Seth R (Wolters Kluwer Medknow Publications, 2008)
Background: This study was designed to compare the success rate of biological and composite restorations when used to replace structural loss of primary anterior teeth using intracanal post for radicular support of the restoration. Materials and Methods: Forty-two patients aged between 3-5 years presenting with early childhood caries (ECC) received at least one or more composite and biological restorations for comparative evaluation. A total of 150 restorations were done (75 biological restorations and 75 composite restorations). The restorations were evaluated single-blind according to a modified USPHS system. Assessment of the patient′s response in accepting a biological restoration, psychological impact of the restorations, view of the parents, and peer group reviews, etc. were recorded in a response sheet in presence of the child and the parents. Observations and Results: In vivo clinical performance of biological post and crown restorations and intracanal reinforced composite restorations was comparable with respect to shade match, marginal discoloration, marginal integrity, surface finish, gingival health, retention, and recurrent carious lesions. The cost effectiveness of biological restorations was certainly a positive attribute. Conclusion: The biological restoration presented as a cost effective, clinician friendly, less-technique sensitive, and esthetic alternative to commercially available restorative materials used for restoring deciduous teeth affected by ECC.